Evaluation of stroke health education for primary school students in Dali, China - Yang, Yunjuan; Dai, Jing; Min, Jieqing; Song, Zhizhong; Zha, Shun; Chang, Litao; Chai, Jiajia; Yang, Youpei; Liu, Yang; Zhang, Xin; Wu, Xiyun; Gong, Yuwen; et al. (Frontiers in Public Health, 2022)
Objectives To provide us with some evidence to develop more targeted stroke intervention strategies, improve the health awareness of stroke among children, and advocate the health promotion campaign of “small hands holding big hands” among parents and children, we have conducted a health education program on stroke among primary school students in Dali. Methods This study has applied stratified random cluster sampling in Dali of Yunnan, China. We compared the improvement of students' knowledge of stroke before and after our health education program in primary school students of Dali in October 2020. Data were collected through 3 rounds of survey by using the same questionnaire. Results There were 215 participants aged 7–8 years old sampled in the first phase of the study and 145 participants in the follow-up study. The knowledge of stroke among the participants was relatively low in the pre-intervention survey. After the health education, all the indicators on stroke knowledge were improved. The correct rates in stroke definition, sequelae, and “1-2-0” identification were increased from 0 to 66.05%, to 53.95% and 64.19%, respectively, in both pre-intervention and post-intervention surveys. The correct rate of stroke knowledge was about 4.83–92.41% 3 months after the intervention. The mean score of the questionnaire was 4.25 ± 0.19 in the pre-intervention survey, and that was 15.85 ±0.27 in the post-intervention one. The mean score was 14.02 ± 0.28 post-3-month test. The score in the 3-month survey after the intervention was 11.55% lower than that in the post-intervention score. Conclusions The effect of stroke-related knowledge in the health education program for children is improved significantly and this can last for 3 months but it also had attenuation. We should repeat pertinent health education among students.